Naina V/S Kyra: A Comparative Analysis of Engagement Metrics to Uncover the Most Desired Female Virtual Influencer in India (Journal of Informatics Education and Research, 2025)
The rise of Virtual Influencers has completely altered the landscape of Influencer Marketing. Talking about the digital landscape in India, these AI generated characters possess personality and attributes similar to humans and are being extensively used for Brand promotions. This paper uncovers the evolving dynamics of AI influencers in Indian market by analysing the social media engagement of India’s two leading female Virtual Influencers Kyra and Naina in order to understand whom they audience perceives more likeable and desired. Moreover, this research entails the use of content analysis method which explores the likes, comments, shares as well as the video views of the brand collaboration on their Instagram handles of these two female virtual influencers- Kyra and Naina. The time frame chosen for administering this analysis is over a span of two months. Furthermore, this research intends to investigate the engagement metrics of these two virtual influencers, the preferences and perception of social media users as well as it apprehends the most desired virtual influencer in India.